Preliminary evaluation of thrust loss in commercial aircraft engine due to airborne collision with Unmanned Aerial Vehicles (UAVs) - Mohd Hasrizam Che Man (2021)
This paper is devoted to investigating the influence of UAVs airborne collision with civil aircraft engine on the operation safety of commercial aircraft. The damage levels of the civil aircraft fan blades and compressor blades during the UAVs airborne collision are both evaluated based on the Finite Element Method (FEM) simulation. Besides, the percentage of the engine thrust loss can be estimated by the reduction of pressure ratio throughout the engine using Computational Fluid Dynamics (CFD) simulation. In our study, it is found that UAVs ingestion at approach flight phase has the highest UAVs debris weight of 80g which can cause most severe damage to aircraft Inlet Guide Vane (IGV) Low Pressure Compressor (LPC) blades. This thrust loss can reach up to 75% when the damage of High Pressure Compressor (HPC) blades is included in the analysis. More simulations are will be carefully carried out to check the reliability of this conclusion, in which the influence of secondary level of damage especially IGV blades debris impact on HPC blades are considered.